(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study aims at identifying the extent to which the postgraduate students in the Faculty of Computer Engineering at the University of Damascus possess the skills of using the computer by measuring their ability in using the computer according to the following fields: (Computer skills, computer skills, operating system skills, skills of using ready software, and skills of using the information network and the Internet). A special questionnaire was constructed to achieve the objectives of the study and presented to a group of competent arbitrators with the expertise to verify its validity and consistency. , Where the stability coefficient (0.94) was also used, and the Statistical Package Program (SPSS) was used to analyze the data Finally, the study led to a number of results which, in turn, led to some suggestions that could benefit computer workers, professionals and specialists in college, university and society.